Characterization and the effect of waste plastic oil in a diesel engine / Muhammad Ahmad Salman Hisham - Muhammad Ahmad Salman, Hisham (2022)
The world currently relies heavily on conventional fuels such as diesel and petrol for its main source of energy supply. This has affected the environmental balance as has caused climate change and environmental pollution. Pollution such as plastic waste is also very common, leading to ocean bio habitat and ecosystems damage. Currently the solution to such plastic pollution is by burial in large landfills or by incineration. An innovative idea has come up in recent years in utilising the waste plastics into usable fuel, solving two of the largest issues faced by the global community with a solution. The purpose of this study is to investigate the suitability of Waste Plastic Oil (WPO) and various proportions of blends between WPO and Waste Cooking Biodiesel (WCB) as fuel in diesel engines. Sample of Malaysian pump diesel of B10, 100% Waste Plastic Oil (WPO) as well as samples of blend WPO 90 (90% waste plastic oil, 10% waste cooking biodiesel), WPO 80 (80% waste plastic oil, 20% waste cooking biodiesel) and WPO 70 (70% waste plastic oil, 30% waste cooking biodiesel) were tested for lubricity. The samples tested were then further analysed and undergone engine testing to determine the engine performance running on the respective fuels. Among the tested samples, all well capable of achieving the lubricity and performance similar to or better than of the B10 diesel. The fuels calorific values showed a decreasing trend with increasing WCB content. Content on pollutants such as eicosane tend to be higher with blends with lower WCB content. The physical property of the WPO 90 and the added advantage in terms of its fuel consumption placed it the most suitable fuel to replace the currently available B10 diesel in the market.